SIMULASI UJI IMPACT PADA DESAIN VELG BERBAHAN ASTM A299 DENGAN DIAMETER 15 INCH DENGAN STANDARD UJI SAE J175 - Dedi Sofyan; Adhes Gamayel; Mohamad Zaenudin (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2023)
Car wheels have an important role in supporting the load of the vehicle, so the wheels are required to have the strength and design that can withstand the weight of the vehicle. Good wheels must be able to withstand the weight of the vehicle as well as the collisions that occur during the use period. The collision that occurs will cause stress on the wheel material. The magnitude of the stress can be simulated using computer-aided engineering (CAE)-based software. This study simulated collisions in the case of an impact test with the SAE 175 standard, with an impact of 3200 Newton, and the wheel material used was ASTM A299, which has an elastic modulus of 200 GPa and a yield strength of 275 MPa. The wheel design has a design difference that lies in the V-shaped spokes, with the V angle for the model 1 wheel being 22°, the model 2 wheel being 50°, and the model 3 wheel being 90°. The simulation results on the values of stress and strain show that the greater the value of the V angle of the wheel, the smaller the value of the stress and strain produced due to the collisions imposed on the wheel. This is due to the better ability of the wheel design with a larger wheel V angle value to spread the stress and not accumulate at a critical point